Mechanical strength of quartz reinforced polyvinyl acetate/leaves-waste composite. (June 2020) - Masturi,; Alighiri, D; Susilawati,; Sunarno,
Abstract: A quartz reinforced polyvinyl acetate/leaves-waste composite has been made using simple pressing method. This work was performed as an answer for the solid waste abundance and deforestation activity. Having been wet-milled using ethanol 70% and dried for 4 days, the quartz was added as reinforcement in polyvinyl acetate (PVAc)/leaves waste mixture with varied contents to form PVAc/leaves waste/quartz composite via pressing at 5 metric ton for 20 minutes. The compressive strength test shows the mechanical strength varies from 35.53 to 39.93 MPA as quartz contents, with a sample having quartz sand content 4.60 × 10 −3 (w/w) has maximum mechanical strength as 39.93 MPa, and the addition of quartz above the content makes the mechanical strength tends to decrease. The strength values are comparable to some previous works by several authors and some building materials, such Sago pulp composite, polyurethane/solid waste/nanosilica composite, agriculture-waste/silica composite, soil brick, limestone, natural fiber reinforced concrete and Portland cement concrete. This result shows the quartz reinforced polyvinyl acetate/leaves-waste composite has been acceptable to compete the woods as building materials to reduce deforestation.